TAX AMNESTY, KEPATUHAN WP DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK DI KPP LUBUK PAKAM - Iman Indrafana Kusumo Hasbullah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
Tax is one of the state revenues used to finance Anggaran Pendapatan Belanja Negara (APBN). This research was conducted to analyze the effect of tax amnesty, taxpayer compliance and tax audit on tax revenues in KPP Pratama Lubuk Pakam. Research uses causality methods, with primary data, using a questionnaire. The population of this research is taxpayers in KPP Pratama Lubuk Pakam. The research data analysis technique uses a regression model. The results of the study, it shows that tax amnesty does not have a significant effect on tax revenue, taxpayer compliance has a significant effect on tax revenue, and tax audit does not have a significant effect on tax revenue in KPP Pratama Lubuk Pakam. In coefficient of determination, the value of adjusted coefficient R square (R2) is equal to 0.082 indicates that tax revenue in KPP Pratama Lubuk Pakam can be explained by tax amnesty, taxpayer compliance and tax audit 8.2% and the remaining 91.8% explained by variable others that are not examined.